2016
DOI: 10.3390/rs8120999
|View full text |Cite
|
Sign up to set email alerts
|

Stage Monitoring in Turbid Reservoirs with an Inclined Terrestrial Near-Infrared Lidar

Abstract: Abstract:To monitor the stage in turbid reservoirs with a sloping bank, it has been proposed to install a near-infrared Lidar on the bank and to orient it so that it points at the water surface with a large incidence angle (between ≈ 30 • and 70 • ). The technique assumes that the Lidar can detect suspended particles that are slightly below the water surface. Some laboratory results and the first long-term assessment (>2 years) of the technique are presented. It found that: (1) although the test Lidar provides… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(23 citation statements)
references
References 23 publications
2
21
0
Order By: Relevance
“…As shown in a previous study [16], both parameters can be obtained empirically through calibration when at least two reference stage data are available. However, it is difficult to obtain reference stage data during the passing of a flash flood.…”
Section: One-point Calibrationmentioning
confidence: 99%
See 3 more Smart Citations
“…As shown in a previous study [16], both parameters can be obtained empirically through calibration when at least two reference stage data are available. However, it is difficult to obtain reference stage data during the passing of a flash flood.…”
Section: One-point Calibrationmentioning
confidence: 99%
“…As an example of application, let us consider: U(D) = 0.08 m and U(θ) = 0.01 rad (≈0.6 • ), which can easily be attained in practice [16]. In this case, and for a Lidar with an incidence angle of θ = 65 • , the uncertainty of the stage estimates should be 0.05 m during low-water periods and should increase up to ≈0.15 m if the stage reaches 6 m (Figure 1), which is an extreme case (return period > 50 years) for the river described herein.…”
Section: One-point Calibrationmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast to other remote sensing tools (e.g., RaDAR, video camera), 2D scanners are capable of accurately measuring surf zone wave geometry. In freshwater conditions where the presence of foam or air bubbles (required to scatter the incident laser) is scarcer, single point LiDAR has applications for steady water body monitoring [10] as well as for more dynamical systems such as flash floods [11]. In laboratory conditions, Martins, K. et al [12] demonstrated the potential of 2D LiDAR to describe the geometry of breaking waves at prototype scale.…”
Section: Introductionmentioning
confidence: 99%